COVID-19 Vaccination in Fragile Patients: Current Evidence and an Harmonized Transdisease Trial - Agrati, Chiara; Di Cosimo, Serena; Fenoglio, Daniela; Apolone, Giovanni; Ciceri, Fabio; Ciliberto, Gennaro; Baldanti, Fausto; Costantini, Massimo; Giannarelli, Diana; Ippolito, Giuseppe; Locatelli, Franco; Mantovani, Alberto; et al. (Frontiers in Immunology, 2021)
Patients diagnosed with malignancy, neurological and immunological disorders, i.e., fragile patients, have been excluded from COVID-19 vaccine trials. However, this population may present immune response abnormalities, and relative reduced vaccine responsiveness. Here we review the limited current evidence on the immune responses to vaccination of patients with different underlying diseases. To address open questions we present the VAX4FRAIL study aimed at assessing immune responses to vaccination in a large transdisease cohort of patients with cancer, neurological and rheumatological diseases.